2021
DOI: 10.1007/s10565-021-09640-x
|View full text |Cite|
|
Sign up to set email alerts
|

Exploring the ATR-CHK1 pathway in the response of doxorubicin-induced DNA damages in acute lymphoblastic leukemia cells

Abstract: Doxorubicin (Dox) is one of the most commonly used anthracyclines for the treatment of solid and hematological tumors such as B−/T cell acute lymphoblastic leukemia (ALL). Dox compromises topoisomerase II enzyme functionality, thus inducing structural damages during DNA replication and causes direct damages intercalating into DNA double helix. Eukaryotic cells respond to DNA damages by activating the ATM-CHK2 and/or ATR-CHK1 pathway, whose function is to regulate cell cycle progression, to promote damage repai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 56 publications
2
5
0
Order By: Relevance
“…The heat generated by the PDA shell layer under NIR light enhanced the toxicity and chemical reactions between the drug and the DNA of HeLa cells and inhibited the activity of DNA repair enzymes in post-chemotherapy lesions. 41 It disrupted the synthesis and repair of tumor cell DNA and led to death of HeLa cells. 42 In Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The heat generated by the PDA shell layer under NIR light enhanced the toxicity and chemical reactions between the drug and the DNA of HeLa cells and inhibited the activity of DNA repair enzymes in post-chemotherapy lesions. 41 It disrupted the synthesis and repair of tumor cell DNA and led to death of HeLa cells. 42 In Fig.…”
Section: Resultsmentioning
confidence: 99%
“…From a chemical structure perspective, tryptanthrin, like the TopoI inhibitor camptothecins and the TopoII inhibitor doxorubicin, possesses a planar polycyclic structure. Although camptothecins and doxorubicin have different molecular mechanisms, both can induce DNA damage and G2/M cell cycle arrest [ 36 , 37 ]. Interestingly, previous studies have shown that ALL cells respond to doxorubicin-induced DNA damages by activating the ATR-CHK1 pathway [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although camptothecins and doxorubicin have different molecular mechanisms, both can induce DNA damage and G2/M cell cycle arrest [ 36 , 37 ]. Interestingly, previous studies have shown that ALL cells respond to doxorubicin-induced DNA damages by activating the ATR-CHK1 pathway [ 36 ]. Additionally, derivatives of tryptanthrin have also been found to exhibit inhibitory effects on TopoII [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…In B-ALL cells, as with AML, the pol 1 inhibitor CX5461 activates the ATR pathway and mediates G2 checkpoint arrest, and thus induced apoptosis synergistically in combination with VE-822 ( 45 ), providing another alternative combination strategy through exacerbation of replication stress. Treatment of ALL cell lines and primary ALL cells with VE-821 in combination with doxorubicin also proved effective ( 46 ).…”
Section: Pre-clinical Data For Ddr Inhibitors In Hematological Cancersmentioning
confidence: 99%
“…In cell lines prexasertib was synergistic with the tyrosine kinase inhibitor, imatinib, and purine nucleoside antimetabolite, clofarabine, with the prexasertib/imatinib combination also showing activity against primary leukemic blasts ( 84 ). Prexasertib, also acted as chemosensitizer in combination with doxorubicin in ALL cell lines and primary ALL cells ( 46 ). The combination of CHK1 inhibition with other targeted agents as well as immunotherapies against ALL are likely to be more promising than their combination with cytotoxic agents given the hematologic toxicity and the chemo resistant nature of the relapsed ALL.…”
Section: Pre-clinical Data For Ddr Inhibitors In Hematological Cancersmentioning
confidence: 99%